A Spanish three model unit on food: a teaching philosophy with complementary instructional practices - Cox, Chelsea L. (Kansas State University, 2011)
In this report, I present my personal teaching philosophy and the instructional practices that I believe best contribute to a successful second language classroom. Comprising the teaching philosophy chapter are sections concerning: the role of the instructor, the three parameters of post-method pedagogy, the maximization of learning opportunities and minimalization of perceptual mismatches, the need for negotiated interaction, the promotion of learner autonomy, the teaching of higher order thinking skills, the advantages of contextualized input, and the development of students' cultural consciousness. The instructional practices chapter describes my approach to grammar instruction, vocabulary instruction and the implementation of authentic texts. To conclude, I offer a model five-day lesson plan, complete with structured pedagogical activities, contextualized to the theme of food, which will integrate the ideas and concepts discussed in the philosophy and practices chapters.
Keywords: Second language acquisition; Teaching philosophy; Instructional practices; Spanish; Foreign Language Instruction (0444); Language, Modern (0291); Pedagogy (0456)